AIM in Wearable and Implantable Computing - Baronetto, Annalisa; Amft, Oliver (Springer International Publishing, 2022)
Wearable and implantable computing devices are becoming an integral component in healthcare thanks to their ability to measure multiple physical, physiological, and environmental variables in everyday life. The analysis of the large volume, velocity, and variety of data requires AI methods and context awareness. Body-worn computing devices can help clinicians by providing important information in decision-making, e.g., during diagnosis and therapy management, but similarly could help to implement interventions, e.g., to provide reminders and nudges. This chapter gives an overview on AI-empowered wearable and implantable computing systems and their use in medicine. First, context awareness and its implementation is introduced. AI application examples are detailed. Subsequently, AI methods for personalization and optimal system design are reviewed, including methods for fabrication planning and monitoring. The chapter is concluded by discussing procedures to validate medical wearable and implantable systems, from safety assessments to usability tests.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Edge computing; Edge intelligence; Embedded systems; Medical wearables; Smart clothing; Smart textiles; Ubiquitous computing; Wearable computing